Peningkatan Literasi Sains melalui Pembelajaran Kreatif Berbasis Inovasi dan Teknologi Ramah Lingkungan: Pengabdian - Katarina Varmina Doa Liza; Maria Selviana Taal; Nining Sariyyah; Chatarina Novianti; Maria Nurisa (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Elementary schools are the primary target of this PKM because science learning needs to be adapted to the characteristics of student development through creative approaches and innovative media. This activity aims to improve elementary school students' scientific literacy through creative learning based on innovation and environmentally friendly technology. Initial observations at SDI Tongatey showed low student understanding of the digestive system, the sense of hearing, and biotic and abiotic components due to limited interesting and contextual learning media. The methods applied included developing teaching media, demonstrating simple teaching aids made from recycled materials, utilizing digital applications such as Assembler, Zep, and Worldwall, and mentoring through observation and discussion. The results of the activity showed an 80% increase in conceptual understanding, marked by students' ability to explain the digestive process, ear structure, and biotic-abiotic differences, accompanied by increased student enthusiasm and activeness. In addition, teachers acquired new skills in the use of digital media and environmentally friendly technology. Overall, this program effectively increased elementary school students' scientific literacy and learning motivation.